The Urgency of Vocational Higher Education to Restore the Magnificence of ‘Pasar Rakyat’ in Indonesia - Rahayu, S; Dachlan, A N (KnE Social Sciences, 2018)
Framing analysis offers a way to describe the power of a communicating text. This study tries to utilize that to synthesize the urgency of vocational higher education to restore the magnificence of ’Pasar Rakyat’ in Indonesia. Especially, in terms of community market management. This research will use framing analytical method, put forward by Robert N. Entman, on the news in various digital mass media from January to February 2017. The framing analysis will be done with four framing components, namely: (1) problem identification, which emphasizes why vocational higher education can restore the glory of Pasar Rakyat in Indonesia; (2) causal interpretation, what and who should be targeted by vocational higher education in this effort; (3) moral evaluation, related to the ideal character that must be strived to emerge from the manager of ‘pasar rakyat’; and (4) treatment recommendation, which emphasizes that vocational higher education can restore the magnificence of the Pasar Rakyat in Indonesia. This research is expected to contribute in the form of the potential of management of ‘pasar rakyat’ as future skills that can be developed in vocational higher education. So that the standardization of community market management is evenly spread throughout Indonesia. Keywords: framing analysis, pasar rakyat, vocational higher education, revitalization